The Impact of Digitalization of Human Resources, Diversity, Inclusion, Knowledge Management and Organizational Structure on Power Company Competition - Mulisa, Serly Ana; Hamdani, Hamdani; Zatira, Dhea (Universitas Muhammadiyah Sorong, 2025)
This study aims to determine the effect of HR digitalization, diversity, inclusion, knowledge management and organizational structure on the competitiveness of companies at PT. Toko Halo Indonesia. The method used in this study is the multiple regression analysis method with a quantitative descriptive research type. The population in this study were employees of PT. Toko Halo Indonesia totaling 177. Based on the proportional stratified random sampling method, the research sample to be taken from the population is 177 respondents. The data analysis technique used is quantitative descriptive statistical analysis, using IBM SPSS version 26. The results of this study indicate that the variables of HR digitalization, diversity, inclusion, knowledge management and organizational structure on company competitiveness (Y) are indicated by the Fcount>Ftable value of 739.017> 2.72 with a significant value of 0.000 <0.05. Based on the results of the study, it can be concluded that the impact of HR digitalization, diversity, inclusion, knowledge management and organizational structure has a significant influence on company competitiveness. Companies that are able to integrate all these aspects will be better prepared to compete in an increasingly competitive market. These findings indicate that companies need to adopt a comprehensive digital strategy and create an inclusive work environment to increase competitiveness. Investment in digital skills training and the development of an organizational culture that supports diversity will be key to facing challenges in the digital era. Further research is recommended to explore the relationship between these factors in different industries.